Environment Niche Perspective on Brown Canyon Post-Mining Area in Semarang City (Forum Ilmu Sosial, 2022)
Post-mining activities are essential to prevent the negative impacts based on the restoration design. Mining issues encourage residents to establish alternative post-mining tourism management slowly. The idea was proposed to respond to the socio-ecological crisis around the left area. This study aims to 1) analyze the socio-ecological crises in the mining area and 2) analyze the post-mining utilization strategies for Brown Canyon as a tourism destination. This research was qualitative. Data collection was done through observation, interviews, and documentation. Data validity was tested by using triangulation. The analytical method was Miles and Huberman's model by conducting the analysis process. The primary components are data collection, reduction, presentation, and conclusion. The results were analyzed using the rational choice theory by James A. Coleman and the environment niche theory by Nugroho Trisnu Brata. The results point out that the mining’s in Rowosari Village bring both positive and negative impacts. It is positive as it provides job opportunities for people. At the same time, it is harmful as it threats the sustainability of socio-ecological life, such as loss of tree landscapes, landslides, noise pollution, and air pollution. The socio-ecological crises gave rise to the idea of carrying out post-mining activities as a strategy to build a tourism destination—a reasonable choice for the government, mine owners, and the community. Until now, the community is still planning a post-mining strategy to take advantage of environmental gaps despite various obstacles, such as illegal levies, inconsistencies in the direction of post-mining, and ongoing illegal mining activities.